A recurrent algorithm for spectrum estimation - Kazlauskas, Kazys; Kazlauskas, Jaunius; Petreikytė, Gintarė (Lietuvos matematikos rinkinys, 2009)
A recurrent algorithm for spectrum estimation is proposed. The efficiency of the algorithm is investigated and results of computational experiments are given.
Keywords: spectrum estimation; inverse matrix; recurrent algorithm